Series phased-mission systems with heterogeneous warm standby components. (July 2020) - Levitin, Gregory; Xing, Liudong; Xiang, Yanping
Highlights: A new type of series phased-mission systems is modeled and optimized. Heterogeneous warm standby configuration for each phase component is considered. An event transition-based method to evaluate the mission success probability is proposed. The optimal element loading problem is formulated and solved. The element sensitivity analysis is performed to rank importance of each element. Abstract: In many industrial and aerospace systems, multiple and non-overlapping phases of operations must be performed consecutively, and each phase is performed by a different component. The mission succeeds only when each component successfully accomplishes the subtask assigned to its phase. Such systems are referred to as series phased-mission systems (SPMSs). To enhance the reliability of each phase and thus the entire mission, 1-out-of- N warm standby configuration is implemented for each phase component, with one element working and online when the phase is active and the rest of elements waiting in the standby mode. Different elements may have different failure behaviors and performances. An event transition-based method is proposed to evaluate the mission success probability (MSP) of the considered SPMS with heterogeneous warm standby components. The optimal element loading problem is then solved, which finds the load level of each element to maximize the MSP. The element sensitivity analysis is also performed to rank importance of each element by its impact on the MSP. Interactions between sensitivity analysis results and element activation sequences within each component are further studied through examples.